A Model for Analysis of Environmental Accidents Based on Fuzzy Logic: Case Study: Exxon Valdez Oil Spill - Golzio, Ana Claudia [UNESP]; Puerta-Díaz, Mirelys [UNESP] (Springer Nature, 2021)
This research aims to present a fuzzy-logic-based conceptual model for environmental accidents analysis, to reveal corporate social responsibility initiatives by companies responsible for the disasters. We studied one of the biggest environmental man-made disasters in history, the one that occurred on March 24, 1989 in Prince William Sound, Alaska when the oil tanker Exxon Valdez spilled 10.8 million gallons of American crude oil. The data was collected from the online database of the newspaper The New York Times for the timespan 03/24/1989–09/01/2017. As a central point of the research, we investigate ethical issues based on the mapping of an ethical vocabulary carried out in the corpus of the analyzed documents. The results show that the proposed model can be replicated, after some adjustments, to verify actions in accordance with the principles of corporate social responsibility for other environmental accidents.
Keywords: Corporate social responsibility; Data mining; Fuzzy Rules-Based System